Analisis Strategi Pengembangan Pariwisata Halal Pada Dinas Kepemudaan Olahraga Kebudayaan dan Pariwisata Kota Tasikmalaya - Nursyifa Fitri Suryani; Rima Rahayu; Wulansari; Lina Marlina (Niqosiya: Journal of Economics and Business Research, 2023)
Tasikmalaya has great potential as a halal tourism destination. DISPORABUDPAR plays an important role in the halal tourism development strategy in Tasikmlaya City. This research method uses descriptive qualitative with the researcher as the main instrument and applies triangulation techniques. Data was obtained from primary data through direct observation and interviews with employees, as well as secondary data from literature related to halal tourism. The results of this research, DISPORABUDPAR Tasikmalaya City, have succeeded in creating a conducive environment for halal tourism through strategies that can support the sustainability of halal tourism, namely through programs such as COET, socialization of halal certificates, and construction of infrastructure. Even though it has succeeded in attracting the attention of tourists, budget constraints and the unwillingness of some sellers to receive halal certification need to be overcome so that the development of halal tourism continues. Coordination with stakeholders is very important to strengthen Tasikmalaya City's position as a halal tourism model.